ALGORITMA SEQUENTIAL SEARCH DAN BINARY SEARCH PADA SISTEM PENCARIAN E-ARSIP BERBASIS WEB - ismail ismail ismail (Lambung Mangkurat University, 2022)
The National University Biology Graduate School has been operating for a long time and has produced many graduates, from the implementation of activities many files and archives have been issued and accepted. Unfortunately, it is still traditionally recorded manually in a ledger, there is no computerized archive management. Based on the background of the problem, the researcher made a web-based letter search application in the administration of the National University Graduate School. The purpose of the application is to facilitate the filing and search of letters carried out by administrative staff to search for letters stored in the electronic archive system. The method we will use is the Sequential Search Algorithm and Binary Search. Sequential Search is used if the data is in a random state or not in order, while Binary Search is used for data that is already in sequence. where to display binary data the total time is 292.9ms to display data and for sequential search 317ms. From the results of research binary search is more efficient to search data.Keywords: Search application. Sequential Search and Binary Search Algorithms.Sekolah Pascasarjana Biologi Univeritas Nasional sudah lama beroperasi dan telah banyak meghasilkan lulusan, dari penyelenggaraan kegiatan banyak berkas dan arsip yang telah dikeluarkan dan diterima. sayangnya masih didata secara tradisional dengan cara manual dicatat didalam buku besar tidak adanya pengelolaan arsip dilakukan secara terkomputerisasi. Berdasarkan latar belakang masalah tersebut peneliti membuat aplikasi pencarian surat berbasis web di administrasi Sekolah Pascasarjana Universitas nasional. Tujuan dari aplikasi tersebut adalah untuk mempermudah pengarsipan dan pencarian surat yang dilakukan oleh staff administrasi untuk mencari surat yang tersimpan pada sistem arsip elektronik. Metode yang akan kami gunakan adalah Algoritma Sequential Search dan Binary Search. Sequential Search digunakan apabila data dalam keadaan acak atau tidak urut sedangkan Binary Search digunakan pada data yang sudah dalam keadaan urut. dimana untuk menampilkan data binary total waktu 292.9ms untuk menapilkan data dan untuk sequential search 317ms. Dari hasil penelitian binary search lebih efisien untuk melakukan pencariian data.Kata Kunci : Pencarian surat. Algoritma Sequential Search dan Binary Search.